Reflexão sobre as dificuldades encontradas nas práticas docentes em aulas de Ciências durante a pandemia do Covid-19 no ano de 2020 em escolas do meio rural - BORGES, Ivanilde Silvia Araujo (2022)
The covid-19 pandemic caused several changes within society, directly affecting education in all its sectors and all different modalities, it was necessary to make several adaptations because of the pandemic, one of these was remote teaching that emerged as a possibility of bring students and teachers together at the time of social isolation. The present work proposes to analyze how remote teaching happened in schools in the rural environment and how the process of adapting teachers to the necessary technologies was, for that, interviews were carried out with professionals in the field of education and the qualitative method was used to analyze the Dice. Interviews were carried out with two teachers and with that we realized that education in the times of the covid 19 pandemic suffered great impacts with the distance of teachers and students. The work is willing to show how education teachers dealt with the difficulties encountered due to the distance caused by the pandemic.